Students’ perceptions of their STEM learning environment - Fairhurst, Nicole; Koul, Rekha; Sheffield, Rachel (2023)
Australia’s economic need for innovation has led to Science, Technology, Engineering and Mathematics (STEM) education becoming an essential investment for the future. This study utilised a mixed-methods approach involving a pre-validated quantitative questionnaire together with qualitative semi-structured focus groups with students across four Year 5 classrooms. Students provided their perceptions of their STEM learning environment and their interactions with their teacher to identify factors influencing their engagement for pursuing these disciplines. The questionnaire comprised of scales from three different instruments: Classroom Emotional Climate, Test of Science Related Attitudes, and Questionnaire on Teacher Interaction. Several key factors were identified through student responses, including Student Freedom, Peer Collaboration, Problem Solving, Communication, Time, and Preferred Environments. 33 out of possible 40 correlations between scales were statistically significant, but eta2 values were considered low (0.12–0.37). Overall, the students expressed positive perceptions about their STEM learning environment, with Student Freedom, Peer Collaboration, Problem Solving, Communication and Time appearing to impact their perceptions of STEM education. Three focus groups with a total of 12 students identified suggestions for improving STEM learning environments. Implications from this research include the importance of considering student perceptions when measuring the quality of STEM learning environments, as well as how facets of these environments can impact student attitudes towards STEM.